Acidity Level and Cooking Mark Beef Nugget With Different Types of Flour - Harapin Hafid; Yulianti Yulianti; Astriana Napirah (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
The study aimed to know physic and organoleptic characteristic of beef nugget using different flour. The variable of this study were physic characteristics and organoleptic characteristics. The treatment of this study used different as a filler, were wheat flour, maizena flour, jack fruit seeds flour, and tapioka flour. The data analysis of the study using fully randomized design and least significantly different (LSD) test as post hoc. The result of the study showed using of different flour were wheat flour, maizena flour, jack fruit seeds flour, and tapioka flour, was not significanly different (p>0,05) for pH, cooking lost, aroma, color, and acceptability beef nugget, but very significantly different (p<0,01) for beef nugget flavor, and significantly different (p<0,05) for tenderness and texture of beef nugget.